Benchmarking Scalability of Message Transport Systems in the JADE Platform: Experimental Evaluation and Performance Analysis - Sgursky, Luis Felipe Ferin; Casals, Arthur; Brandao, Anarosa Alves Franco (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2023: Anais do XVII Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2023)
Agents are distinct entities known for their independence and autonomy. In a multi-agent system, multiple agents can interact with each other. In this context, communication is a crucial component in enabling relationships between agents, and it is one of the fundamental features provided by a multiagent system platform. As such, the performance of a multi-agent system can be directly affected by the implementation of its communication mechanism. In this paper, we analyze the scalability of the JADE platform from the perspective of its communication mechanism. We do this by defining benchmarks and evaluating the platform’s response in different scale-up and scale-out scenarios.